Reconstruction of Criminal Law Regarding Consumer Protection in Peer-to-Peer (P2P) Lending Services in Indonesia, Concerning Balancing Rights and Responsibilities in the Digital Era based on Pancasila Justice - Tegar Harbriyana Putra; Hartiwiningsih; Adriana Grahani Firdausy (Journal of Legal and Cultural Analytics, 2026)
The development of Peer-to-Peer (P2P) Lending services in Indonesia has increased financial accessibility but also created consumer protection issues, including personal data misuse, lack of transparency, and abusive debt collection practices. These problems indicate weaknesses in the existing criminal law framework, which remains unable to adequately address digital-based crimes and regulatory fragmentation. This study aims to analyze the current construction of criminal law in P2P Lending services, examine the integration of Pancasila justice values, and formulate a reconstruction model that balances consumer rights and provider responsibilities. Using a normative juridical method with statutory, conceptual, and philosophical approaches, the study finds that existing criminal law remains conventional and insufficiently responsive to digital exploitation. Therefore, criminal law reconstruction should integrate legal substance, enforcement mechanisms, institutional structures, and legal culture based on the values of Pancasila. Such reconstruction is expected to create an adaptive, just, and accountable consumer protection system within Indonesia’s fintech ecosystem.